Pemberdayaan Umkm Mikro, Kecil Dan Menengah Untuk Meningkatkan Pendapatan Masyarakat Pada Masa Pandemi (Cilangkahan Malingping Kabupaten Lebak) - Haerani, Anggi; Kurnianingsih, Asih; Nuraisiah, Rohaelis; Noviani, Lona; Rohiyatussakinah, Ina (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Lebak, Banten, Especially in Cilangkahan Village, are one of the sources of community income. Through community service After the Covid-19 pandemic, there has been a decline in sales and this has also reduced community income. The purpose community service report are to know the empowerment of MSMEs during the Covid-19 pandemic; 2) to know the inhibiting factors of MSME empowerment during the Covid-19 pandemic. The activity method used in the community service is counselling on the mechanism of empowering MSMEs in the community during the pandemic. It discussed in the workshop is theory of empowerment through four dimensions, namely Human Development, Business Development, Community Development, and Institutional Development. The activity shows that the empowerment of MSMEs during this pandemic has not been optimal because there are still various obstacles in empowering it. In community service activity, hopefully all the problems faced by the community, especially they will become the concern of many parties; they can help overcome various problems in pandemic. State gradually in this condition, hopefully, MSME players also optimize and more innovative in advancing their businesses support from the government through material support, training, or education. Â Keywords : Empowerment, Community, Pandemic